Tres das en una canoa roja - Williams, Vera B. (New York : Scholastic, 1993)
Mother, Aunt Rosie, and two children make a three-day camping trip by canoe.
Translation of: Three days on a river in a red canoe.
"Reading Rainbow"--Cover.
Keywords: Canoes and canoeing -- Fiction; Camping -- Fiction